Analysis of Jak2 signaling reveals resistance of mouse embryonic hematopoietic stem cells to myeloproliferative disease mutation - Mascarenhas, Maria I. (Blood, 2016)
The regulation of hematopoietic stem cell (HSC) emergence during development provides important information about the basic mechanisms of blood stem cell generation, expansion, and migration. We set out to investigate the role that cytokine signaling pathways play in these early processes and show here that the 2 cytokines interleukin 3 and thrombopoietin have the ability to expand hematopoietic stem and progenitor numbers by regulating their survival and proliferation. For this, they differentially use the Janus kinase (Jak2) and phosphatidylinositol 3-kinase (Pi3k) signaling pathways, with Jak2 mainly relaying the proproliferation signaling, whereas Pi3k mediates the survival signal. Furthermore, using Jak2-deficient embryos, we demonstrate that Jak2 is crucially required for the function of the first HSCs, whereas progenitors are less dependent on Jak2. The JAK2V617F mutation, which renders JAK2 constitutively active and has been linked to myeloproliferative neoplasms, was recently shown to compromise adult HSC function, negatively affecting their repopulation and self-renewal ability, partly through the accumulation of JAK2V617F-induced DNA damage. We report here that nascent HSCs are resistant to the JAK2V617F mutation and show no decrease in repopulation or self-renewal and no increase in DNA damage, even in the presence of 2 mutant copies. More importantly, this unique property of embryonic HSCs is stably maintained through ≥1 round of successive transplantations. In summary, our dissection of cytokine signaling in embryonic HSCs has uncovered unique properties of these cells that are of clinical importance.